The impact of social media influencers’ bragging language styles on consumers’ attitudes toward luxury brands: The dual mediation of envy and trustworthiness - Feng, Wenting; Chang, Dihui; Sun, Hongjie (Frontiers in Psychology, 2023)
In social media, luxury brand managers often use influencers’ bragging word-of-mouth as a marketing tool. Considering the emphasis on modesty as a virtue in the Chinese context, these influencers tend to adopt a humble bragging language style. The research examined the impact of bragging language styles on luxury brands, and proposed that humble bragging, which appeared to be modest, had a negative influence on consumers’ brand attitudes. From the perspective of social comparison theory, we proposed a dual mediation model of malicious envy and trustworthiness to reveal the internal mechanisms and moderating factors of the negative effects of humble bragging. The results of three experiments indicated that, compared with straightforward bragging, when influencers used humble bragging language style, consumers showed higher malicious envy and lower trustworthiness towards influencers, resulting in negative attitudes towards luxury brands adopted by influencers. Moreover, this negative effect was more prominent when influencers had a lower expertise or a higher similarity with consumers. Our findings enriched the antecedents of social media influencer marketing, and provided managers with implications on maximizing the effectiveness of influencer marketing by matching influencers with word-of-mouth content.